The Impact of Climate Change on Rain-Fed Agriculture of Field Crops in Ajloun Governorate (The International Journal for Scientific Research, 2025)
The study aimed to study the impact of climate change on rain-fed agriculture of field crops in Ajloun Governorate, which numbered approximately (6554) farmers, and the study population included all farmers of different demographic characteristics, areas and crops, and the researcher followed the random sample method in distribution, where she distributed (362) copy of the questionnaire to the study sample. The researcher used the statistical analysis program, 25SPSS, to analyze the data collected from the study tool, and used descriptive statistics represented by arithmetic mean, standard deviation, percentages, frequency, relative importance, analysis of Cronbach alpha coefficients, and simple linear regression analysis. The results showed that there is knowledge and awareness among the sample members of climate change and its phenomena. The vast majority had yes answers to a change in some weather phenomena. There has been a change at the beginning and end of winter over the past years. There is also a change in temperatures. The results showed from the point of view of the sample members. The level of climate change impact has a role on the productivity of rain-fed field crops is high, as it achieved an arithmetic average of (3.80), which is within the high relative importance, and in the year (2015) it achieved the highest rainfall rate, while the lowest rainfall rate was in the year 2000, and the highest temperature was recorded in the year (2016) where it reached (18.2) degrees Celsius, while the lowest temperature was in the year (2000), when it reached (12.7) degrees Celsius.  The study recommended the creation of a flexible plan to manage the production of rain-fed field crops according to the emerging conditions of climate change.
Keywords: Climate Change; Field Crops; Rain-Fed Agriculture; Ajloun